1999
DOI: 10.1002/(sici)1096-9071(199911)59:3<281::aid-jmv4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus structural proteins induce liver cell injury in transgenic mice

Abstract: To develop an animal model of hepatitis C virus (HCV) infection, transgenic mice carrying part of the HCV cDNA (C980) encoding HCV-core and envelope proteins under control of the mouse class I major histocompatibility complex gene (H-2K) regulatory region were produced. HCV-C980 RNA and HCV-core protein were present in livers from line H36 as determined by RNase protection assay and immunostaining, respectively. More than 40 animals from line H36 were examined histologically. Most of these H36 mice after 10 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 51 publications
0
20
1
Order By: Relevance
“…In subjects with hepatitis C virus infection, it is suggested that hepatitis C virus core and envelope proteins may be one causative agent of spontaneous liver cell injury by themselves. 21 When filamentous HBsAg particles accumulate in HBV-infected hepatocytes to extremely high levels, the death of hepatocytes will be induced by severely compromised endoplasmic reticulum function. 22 Noticeably, functionally normal HBsAg-positive hepatocytes are exquisitely hypersensitive to destruction, as reported that HBsAg-positive hepatocytes of HBV transgenic mice were hypersensitive to cytolytic effect of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with hepatitis C virus infection, it is suggested that hepatitis C virus core and envelope proteins may be one causative agent of spontaneous liver cell injury by themselves. 21 When filamentous HBsAg particles accumulate in HBV-infected hepatocytes to extremely high levels, the death of hepatocytes will be induced by severely compromised endoplasmic reticulum function. 22 Noticeably, functionally normal HBsAg-positive hepatocytes are exquisitely hypersensitive to destruction, as reported that HBsAg-positive hepatocytes of HBV transgenic mice were hypersensitive to cytolytic effect of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Honda et al reported that liver samples from HCV core-E1-E2 transgenic mice showed higher Fasmediated cell damage compared with non transgenic mice. 13 Dumoulin et al reported that HCV core protein or HCV E2 protein individually do not prevent TNF-␣ or Fas induced-apoptosis in transient transfected HepG2 cells. 14 Lasarte et al reported that a recombinant adenovirus encoding HCV core and E1 proteins protects liver cells from cytokine-induced hepatocellular damage in experimental models of TNF-mediated hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these reported effects of NS proteins on cellular processes, a large and often contradictory body of literature exists concerning the impact of expression of the viral structural proteins on cellular processes. Most prominent and best documented of these is the effect of core protein expression on fatty acid metabolism and storage, resulting in the accumulation of excess numbers of lipid-laden droplets in vitro, and steatosis in transgenic mice (4,22,24,25,40,45). All of these studies suggest the possibility that one or more manifestations of hepatitis C may reflect direct disruption of normal cellular control processes by the viral proteins.…”
mentioning
confidence: 99%